2021
DOI: 10.1186/s13148-021-01060-2
|View full text |Cite
|
Sign up to set email alerts
|

The impact of CBP expression in estrogen receptor-positive breast cancer

Abstract: Background The development of new biomarkers with diagnostic, prognostic and therapeutic prominence will greatly enhance the management of breast cancer (BC). Several reports suggest the involvement of the histone acetyltransferases CREB-binding protein (CBP) and general control non-depressible 5 (GCN5) in tumor formation; however, their clinical significance in BC remains poorly understood. This study aims to investigate the value of CBP and GCN5 as markers and/or targets for BC prognosis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 55 publications
1
15
0
Order By: Relevance
“…A previous study showed that PGC-1α levels were higher in the HER2+ and the basal subtypes than in other subtypes, which also showed poor prognosis in both subtypes [ 112 ]. CREBBP amplification occurs in ER+ and TNBC but not in HER2+ subtypes [ 113 ]. Recently, CREBBP was identified as a novel driver of TNBC progression [ 114 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that PGC-1α levels were higher in the HER2+ and the basal subtypes than in other subtypes, which also showed poor prognosis in both subtypes [ 112 ]. CREBBP amplification occurs in ER+ and TNBC but not in HER2+ subtypes [ 113 ]. Recently, CREBBP was identified as a novel driver of TNBC progression [ 114 ].…”
Section: Discussionmentioning
confidence: 99%
“…The protein was quantified using the DC ™ protein assay kit (Bio-Rad, United States) and Western blot was performed as described previously (Ramadan et al, 2021). The samples containing equal amounts of protein (15-30 μg) were loaded into the gels to be separated on either 8% or 12% SDS polyacrylamide gel and transblotted onto the nitrocellulose membrane (Bio-Rad, United States).…”
Section: Western Blotmentioning
confidence: 99%
“…To study the expression of various protein markers, cells were seeded, treated as mentioned in the comet assay and the total cell lysate was obtained by incubation with lysis buffer (Glycerol, 20% SDS & 1 M Tris, pH 6.8) containing protease inhibitor cocktail (Sigma-Aldrich, USA). Protein was quanti ed using DC TM protein assay kit (Bio-Rad, USA) and Western blot was performed as described previously by Ramadan et al, 2021 [29]. Samples containing equal amounts of protein (15-30 µg) were loaded into the gels to be separated on either 8% or 12% SDS polyacrylamide gel and transblotted onto nitrocellulose membrane (Bio-Rad, USA).…”
Section: Western Blotmentioning
confidence: 99%